(untitled) (Research, Society and Development, 2023)
The mental processes that constitute the Power of Mind use thinking as their primary tool. Thought creates emotions which in turn cause corresponding behavior. Consequently, thoughts act as motivators that propel the individual to action. Therefore, the quality of each piece of thinking is fundamental to its evolution. The child gradually develops the ability to read the mental states of others, relying both on the beliefs he has created about himself according to his thoughts and perceptions and on subconscious actions that affect him unconsciously. The current literature review studies the importance of the Power of Mind (PoM) in the human factor and its relationship with Theory of Mind (ToM) in preschool age. The conclusions of the research reflect the importance of the Power of the Mind in the formation of thoughts, beliefs, and emotions in young children, presenting several methods of utilizing it in the educational process.